Peranan Kepala Persekutuan Hukum Adat Sebagai Mediator Di Negeri Hutumuri Dalam Penyelesaian Sengketa Jual Beli Tanah Dati - Elfransdo Saimima Putra; Jenny Kristiana Matuankotta; Barzah Latupono (TATOHI: Jurnal Ilmu Hukum, 2022)
Introduction: The role of the head of the customary law union as a mediator is to help both parties to the dispute with a family approach.Purposes of the Research: This study aims to identify and explain the role of the Head of the Customary Law Alliance as a mediator in Hutumuri Country in resolving disputes over the sale and purchase of Tanah Dati. Methods of the Research: The research method used is the type of empirical research. The data used in this paper include primary data and secondary data. Techniques Data collection is done by means of field studies and literature studies. Analysis of the materials used in writing this thesis is to use the method of qualitative material analysis.Results of the Research: The results of the study indicate that all problems or disputes related to Dati's land will be resolved at the State Office by the Head of the Customary Law Alliance as a mediator, whose role is to assist the disputing parties by identifying the disputed issues, balancing options, and considering alternatives that can be offered to them. The parties to reach an agreement and only have the authority to provide advice or determine the mediation process in seeking dispute resolution.